Assessment of the Implementation of Policy on Anti-Sexual Harassment in a Nigerian University - Fasanmi, Success Ayodeji; Seyama, Sadi (Research in Social Sciences and Technology, 2024)
Sexual harassment in universities undermines gender equity, safety, and learning. This study assessed the level of implementation of the anti-sexual harassment policy and the influence of implementation of the policy on gender protection of students and staff of Obafemi Awolowo University (OAU), Nigeria. The study was hinged on the feminist theory. The feminist theory considers the plight of any person or people not just women, with a view to destabilizing systems of power and oppression, especially in an academic environment as in this context. The study adopted cross sectional survey research design. The population comprised of 450 students and 200 members of staff (100 teaching and non-teaching staff each) making a total of 650 participants, using a stratified random sampling to ensure proportional representation from the 10 selected faculties. Data was collected using questionnaires and gathered data were analysed using descriptive and inferential statistics. The results identified gaps in initial awareness and understanding of the anti-sexual harassment policy among students and staff which constituted a setback for the implementation. It was equally noted that the policy development process lacked inclusivity, and implementation activities were perceived as insufficient. Since the implementation process was faulty, the policy has not been able to significantly achieve gender protection on the Campus. The students had uncertain views on the policy's impact, while staff had mixed opinions. The study recommended the need to strengthen policy implementation by way of improving communication channels, transparency, stakeholders’ involvement, and monitoring while punitive measures must be enforced when necessary.